Innate Immune Mechanisms to Protect Against Infection at the Human Decidual-Placental Interface - Hoo, Regina; Nakimuli, Annettee; Vento-Tormo, Roser (Frontiers in Immunology, 2020)
During pregnancy, the placenta forms the anatomical barrier between the mother and developing fetus. Infectious agents can potentially breach the placental barrier resulting in pathogenic transmission from mother to fetus. Innate immune responses, orchestrated by maternal and fetal cells at the maternal-fetal interface, are the first line of defence to avoid vertical transmission. Here, we outline the anatomy of the human placenta and uterine lining, the decidua, the innate immune properties present at this boundary and the capacity for pathogen pattern recognition and other host defense strategies during gestation. We highlight the challenges in studying human placental responses to pathogens and vertical transmission using current experimental models. We propose novel experimental strategies to address such limitations.